Reconfiguração da gestão da educação : um estudo de caso na Segunda Coordenadoria Regional de Educação de São Leopoldo/RS - Schmitz, Taís (2013)
This work is process and product of my doctoral research at the Graduate Program in Education at the Pontifical Catholic University of Rio Grande do Sul (PUCRS). The research lies in the field of EducationManagement and Policystudies.Its subject is the reconfiguration of the management of education through relationship of the educational Projectsat state level and the experience of the Second Regional Coordination of Education (2nd CRE) with regard to the public high schools located in São Leopoldo, RS, from 2007 to 2012. In this perspective, this workincluded issues of managerialism to the naturalization of the Democratic Governance discourse under the concept of Democratic Management. One appealed to the analysis of the Government Proposals with respect to the education occurred in the management of Yeda Rorato Crusius (2007-2010) and in the first biennium of the management of Tarso Fernando Herz Genro (2011-2012) management, aiming to identify in these policies its implications, tensions and contradictions for management mechanisms.One analyzed specifically the Rio Grande Lessons Program and the proposal of curriculum restructuringfor Secondary Education. Thus, the thesis that guided the research focuseson the possibility of joint management policies to leverage an adaptation of the Democratic Management mechanisms corroborating to the construction of a new management concept, the Democratic Governance. It is a qualitative research, which used as data collection strategy semi-structured interviews and documents. For data analysis, it was used statistical analysis and the Collective Subject Discourse. This research points out that it is occurring reconfiguring of the education management concept in Rio Grande do Sul.We are experiencing an adaptation of the mechanisms of the Democratic Managementfor the implantation of the Democratic Governance, toward to the product or to the Market that rather than aim the collaboration and improving social quality of the public school, it consolidates strategies that encourage competition among these schools causing the amplification of the differences. This fact allows demystify the used strategies in both managements of being a policy that brought a democratic perspective. The Democratic Management and Governanceconcepts of still seek to get steady being in constant metamorphosis in a way that its terminology merges itself at different moments. However, this movement provides significant advances in fostering contradictory feelings on the subjects, so that they make